THE IMPACT OF THE SIX THINKING HATS STRATEGY ON THE DEVELOPMENT OF CREATIVE THINKING AND THE LEARNING OF SOME BASIC HANDBALL SKILLS FOR STUDENTS - M.M. Mustafa Abdul Shahid Muhammad (Proximus Journal Publishing, 2025)
Thinking abilities and acquiring essential handball skills among students. An experimental methodology was applied, using a two-group design (experimental and control), as it aligns with the nature and objectives of the research. The study population consisted of second-year male students enrolled in the morning program at the Faculty of Physical Education and Sports Sciences, Al Ain Private University, during the academic year 2024–2025. A total of 56 students, representing 37.33% of the total population (150 students), were selected and randomly assigned to two groups: 28 students in the experimental group and 28 in the control group. Findings revealed a significant improvement in the experimental group’s performance, which received instruction based on the Six Thinking Hats model. This group demonstrated superior development in both creative thinking and the mastery of fundamental handball skills namely dribbling, passing, and shooting, compared to the control group that followed conventional teaching methods
Keywords: group; dribbling; shooting; experimental